Efeitos do apoio dos membros superiores sobre a força muscular respiratória e função pulmonar de pacientes com doença pulmonar obstrutiva crônica - Cavalheri, V. [UNESP]; Camillo, C. A.; Brunetto, A. F.; Probst, V. S.; Cipulo Ramos, E. M. [UNESP]; Pitta, F. (Soc Portuguesa Pneumologia, 2010)
Objective: To analyze the effect of arm bracing posture on respiratory muscle strength and pulmonary function in patients with Chronic Obstructive Pulmonary Disease (COPD).Methods: 20 patients with COPD (11 male; 67 +/- 8 years; BMI 24 +/- 3 Kg . m(-2)) were submitted to assessments of Maximal Inspiratory and Expiratory Pressures (MIP and MEP, respectively) and spirometry with and without arm bracing in a random order. The assessment with arm bracing was done on standing position and the height of the support was adjusted at the level of the ulnar styloid process with elbow flexion and trunk anterior inclination of 30 degrees promoting weight discharge in the upper limbs. Assessment without arm bracing was also performed on standing position, however with the arms relaxed alongside the body. The time interval between assessments was one week.Results: MIP, MEP and maximal voluntary ventilation (MW) were higher with arm bracing than without arm bracing (MIP 64 +/- 22 cmH(2)O versus 54 +/- 24 cmH(2)O, p = 0,00001; MEP 104 +/- 37 cmH(2)O versus 92 +/- 37 cmH(2)O, p = 0,00001 and MW 42 +/- 20 L/min versus 38 +/- 20 L/min, p = 0,003). Other variables did not show statistical significant difference.Conclusion: The arm bracing posture resulted in higher capacity to generate force and endurance of the respiratory muscles in patients with COPD. (C) 2009 Published by Elsevier Espana, S.L. on behalf of Sociedade Portuguesa de Pneumologia. All rights reserved.
Effects of arm bracing posture on respiratory muscle strength and pulmonary function in patients with chronic obstructive pulmonary disease
Keywords: Upper limb; Respiratory muscles; Pulmonary function test; Chronic Obstructive Pulmonary Disease